Urban governance through the lens of service delivery monitoring in informal settlements: a case study of Buffalo City - Kente, Masixole (My University, 2022)
The challenge of resolving the problem of social inclusion and redress is such that is at the fore of administering governance globally. Understanding governance as a process that involves multi-stakeholders jointly acting towards the improvement of basic services in informal settlements. This paper analyses the salience of collaborative planning approaches in monitoring service delivery in South Africa’s informal settlements. Using various informal settlements in Buffalo City in the Eastern Cape province as units of analysis; the paper argues for citizen-centric approaches to service delivery monitoring. The research advocates for a bottom-up approach to community development, where all planning decisions and projects are done with the people that are being ‘planned for’ and/or ‘planned with’. It expands on the Upgrading of Informal Settlements Programme (UISP), and it’s attempt to addressing the needs of informal settlement residents. The study findings demonstrate that through the analysis and monitoring of basic services in informal settlements, spaces for community participation and the collaborative strategies, citizens are able to strengthen governance. On the contrary, the study also shows how the attainment of quality basic services provision in informal settlements is constrained by factors including use of old data and lack of citizen involvement in monitoring basic service delivery. These constrains are tributed to the following factors: lack of a clear policy framework that facilitates citizen involvement in monitoring basic service delivery, lack of intergovernmental coordination and institutional capacity to conduct monitoring, and lack of sensible budgeting that is informed by current data towards the provision of basic services in informal settlements. The paper concludes by proposing for the institutionalization of a citizen-driven monitoring tool, redefinition of the framework for intergovernmental cooperation, and the implementation of mechanisms for ensuring a collective approach to improving the quality of basic services in informal settlements.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Urban Studies to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2021